Gastric mucosal interleukine-8 (IL-8) and interleukine-1beta (IL-1ß) levels in atrophic gastritis and gastric carcinoma patients. - Al-Faisal, Abdul Hussain M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Cytokines are the messengers of the immune system.They are mostly secreted by macrophages and lymphocytes and their production is induced in response to injury or infections.Objective: Biopsy speciemens from the middle body of the stomach were obtained from 18 patients with gastric carcinoma, 32 patients with atrophic gastritis, 50 patients with chronic gastritis and 20 healthy subjects and IL-8 and IL-1B levels were detrmined.Methods: Sandwich-type enzyme-linked immunosorbent assay kit was used to determine the IL-8 and IL-1B levels.Results: IL-8 and IL-1B levels were significantly higher in gastric carcinoma patients than patients with atrophic gastritis and both significantly higher than healthy subjects. Conclusions: IL-8 and IL-1B levels were recommended to be used in differentiation between gastric carcinoma and atrophic gastritis.